IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI KURIKULUM MERDEKA PADA SEKOLAH PENGGERAK SMA NEGERI I KOTA TERNATE - Abdullah, Jainudin; Hasim, Rustam (Universitas Khairun, 2024)
This study explains the implementation of character education through the independent curriculum at the driving school of SMA Negeri 1 Ternate City. The objectives of this study are (1). To find out what character values are contained in the independent curriculum at the driving school, (2). To find out the supporting and inhibiting factors in the implementation of character values contained in the independent curriculum of the driving school at SMA Negeri 1 Ternate City.This research method uses a descriptive research type through a qualitative approach. Qualitative research is a descriptive research by analyzing through an inductive approach. This study emphasizes the theoretical basis which functions to be the focus of research when in the field. The place of this research will be carried out at SMA Negeri 1 Ternate City. The time of implementation of this research was carried out for six months from March to August 2024. The subjects of this research were the Principal, Vice Principal for Curriculum, Vice Principal for Student Affairs, and Teachers. Data collection techniques were observation, interviews, and documentation. Data analysis techniques were data reduction, data presentation, and conclusions.The results of this study indicate that, (1). The Independent Curriculum has a positive impact on the character of students at SMA Negeri I Kota Ternate. With a focus on character development, this curriculum encourages students to think creatively and explore various ways to convey their understanding. Experience-based learning and innovative approaches help to awaken students' creativity in finding solutions to problems faced (2). The independent curriculum applies a lot of interaction, competency strengthening to creativity. If implemented properly, it also simultaneously strengthens students' morals, integrity to noble character.